UNILATERAL SPECTACULOTOMY ON A BURMESE PYTHON (Python bivittatus) WITH SUBSPECTACULAR ABSCESS: A CASE REPORT - Puveanthan Nagappan Govendan; Lynn Kaat Laura Kurniawan (Hasanuddin University, 2020)
A three year old female adult albino Python bivittatus weighing 12 kilograms was presented with a chief complaint of right spectacle growth and whitening. The snake also had a respiratory infection which started about 2 weeks prior to being presented. Physical examination showed bubbly nostrils, inflammation on the right eye, inflammation on the right palatum of the oral cavity, and crackling sound during auscultation when exhaling and hissing. The snake was diagnosed with subspectacular abscess and respiratory infection. Spectaculotomy was performed under general and local anesthesia. All abscesses were removed using a sterile sexing probe while continuously flushing the eye. Topical antiseptic was diluted and flushed into the eye before topical antibiotic eye ointment was applied. Post-operative treatment included daily flushing using an intravenous catheter, eye ointment application, and administration of systemic antibiotic and NSAID to treat the co-related respiratory infection. Three weeks after the surgery the snake went through ecdysis, after which the snake regained its appetite and recovery was thereafter significantly improved.